PHYTOCHEMICAL SCREENING AND ANTI-INFLAMMATORY ACTIVITY OF FRACTIONS FROM SAMBUNG RAMBAT (MICANIA CORDATA) LEAF - Harnis, Zola Efa; Sitorus, Panal; Rosidah, Rosidah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study is to evaluate the anti-inflammatory activity of various fractions from Sambung Rambat leaf (Micania cordata) using ethyl acetate, hexane, and water solvent as the solvent. Methods: Investigation of phytochemical compound was using standard phytochemical screening method, while the anti-inflammatory was using the carrageenan-induced paw edema method in animal (rats) model. Results: The phytochemical screening showed that the fractions of M. cordata had a lot of phytochemical compounds such as flavonoids, glycosides, steroids, triterpenoids, tannins, and saponins. Anti-inflammatory assessment showed that the strongest activity of anti-inflammatory produced by ethyl acetate fraction with 200 mg/kg BW dose. Conclusion: This investigation could be concluded that ethyl acetate fraction of M. cordata might be a potential for the treatment of inflammatory.